FENOMENA IMPULSE BUYING (PEMBELIAN TIDAK TERENCANA) PADA PRAKTIK BELANJA ONLINE DITINJAU DARI PERSPEKTIF EKONOMI SYARIAH - Yusniar Yusniar (AL-ILMU, 2021)
Transactions purchasing goods and services in cyberspace are increasing day by day, this makes the issue of impulse buying increasingly popular in the context of consumer behavior. The phenomenon of purchasing goods and services in cyberspace is something that is commonly done by modern society today, especially in the city of Banda Aceh. One of these marketplaces is Tokopedia, which is an online buying and selling site that provides and serves the needs of consumers in various lines and aspects of life, from household needs to other luxury products. The purpose of this study is to analyze and explain the effect of discount prices, customer value, service quality on impulse buying. This study uses a quantitative approach to the type of qualitative research. The research sample of 100 consumers was taken by purposive sampling technique. Based on the research, it is known that the discount factors on consumers' impulse buying have an effect with a contribution of 35.6%. The functional aspect of the customer value factor influences the contribution of the influence of 19.5%. It can be said that discount prices have an effect on impulsive purchases and the frequency of visits has a positive effect on the Tokopedia online site. The limitations of this research are still broad. It is hoped that further research can be more specific regarding the issue of gender and income levels on impulsive buying attitudes.